EFEKTIVITAS BIOHERBISIDA DARI LIMBAH CAIR PULP KAKAO DALAM PENGENDALIAN BERBAGAI JENIS GULMA DI KEBUN MASYARAKAT KECAMATAN DELI TUA KABUPATEN DELI SERDANG - Ulfa, Syarifah Widya (Program Studi Biologi, Fakultas Biologi Universitas Medan Area, 2019)
Weed known as plants that are able to adapt on the rhythm of growth of crops cultivation. The growth of weeds fast, high regeneration power when injured, and was able to bloom even though conditions are harmed by crop cultivation. Physically, weeds compete with the crop cultivation for space, light, and chemically for water, nutrients, gases. The research was done in the Kec.Deliserdang. The time of the research was carried out in May up to September 2018. Methods in this study using Random Design Group, which is composed of 5 treatment and 6 Deuteronomy. treatment with long fermentation liquid waste pulp. The level of intoxication bioherbicide against weeds was observed after 14 days after application assessment scoring system with cocoa. The results obtained in this study indicate that Fermented pulp of cocoa poisoning influence of weeds Ageratum conyzoides, Axonopus compresus, Borreria latifolia, Cyperus kylingia and Paspalum conjugatum. Fermentation efektiv on F3. There are 4 types of weeds that the level of toxicity is higher compared with long fermentation of 1, 2, and 4 weeks. Of the 5 types, bioherbisida pulp of cocoa is very poisoning the type level effective weeds Ageratum conyzoides until 14 days.